Long-Term Trend of Land Surface Thermal States and Its Spatial Variability in the Eastern Region of the Northern Hemisphere - Zhao, Changyu; Chen, Haishan; Sun, Shanlei (Frontiers in Earth Science, 2020)
Soil enthalpy represents the land surface thermal states by combining soil moisture (sum of soil ice and liquid water) and soil temperature into a single variable. This study applied soil moisture and soil temperature outputs from off-line CLM4.0 model to calculate soil enthalpy from 1948 through 2010 and analyzed the contributions of the soil water and temperature to the trends of winter soil enthalpy in Eastern Northern Hemisphere. The results show that an increasing trend of winter soil enthalpy occurred during the period 1979-2010, especially in Eastern Europe (EE), Eastern Mongolia (EM), the India River Plain (IP) and Central Africa (CA). Overall, increases in soil enthalpy are primarily controlled by decreased soil ice over EE and EM and by increased soil temperature over IP, while the increased soil enthalpy over CA is mainly attributed to increases in soil liquid water and soil temperature, whose contributions are roughly equivalent. The roles of soil moisture and soil temperature in soil enthalpy changes exhibit evident regional differences and are generally latitude-dependent, with soil ice and soil temperature the dominant contributors at mid-high latitudes and mid-low latitudes, respectively. More importantly, when under the condition of soil water phase transition soil enthalpy may be served as a better metric to monitor the long-term trend of land surface thermal states than by using soil moisture or soil temperature alone. Therefore, our findings have important implications for soil enthalpy in climate change research (e.g., the impacts of land thermal anomalies on regional and even global climate).